Basic ship theory - Rawson, K. J.; Tupper, E. C. (Boston : Butterworth-Heinemann, 2001)
Rawson and Tupper's Basic Ship Theory, first published in 1968, is widely known as the standard introductory text for naval architecture students, as well as being a useful reference for the more experienced designer. The fifth edition continues to provide a balance between theory and practice. Volume 1 discusses ship geometry and measurement in its more basic concepts, also covering safety issues, structural strength, flotation, trim and stability. Volume 2 expands on the material in Volume 1, covering the dynamics behaviour of marine vehicles, hydrodynamics, manoeuvrability and seakeeping. It concludes with some case studies of particular ship types and a discussion of maritime design. Both volumes feature the importance of considering the environment in design. Basic Ship Theory is an essential tool for undergraduates and national vocational students of naval architecture, maritime studies, ocean and offshore engineering, and this combined hardback version will be of great assistance to practising marine engineers and naval architects. Brand new edition of the leading undergraduate textbook in Naval Architecture. Provides a basis for more advanced theory. Over 500 examples, with answers.
CONTENTS OF VOLUME 1: Foreword; Acknowledgements; Introduction; Symbols and Nomenclature; Art or Science?; Some tools; Flotation and Trim; Stability; Hazards and Protection; The Ship Girder; Structural Design and Analysis; Launching and Docking; The Ship Environment and Human Factors; Answers to problems; Index. -- CONTENTS OF VOLUME 2: Acknowledgements; Introduction; Symbols and Nomenclature; Powering of Ships: general principles; Powering of Ships: application; Seakeeping; Manoevrability; Major Ship Design Features; Ship Design; Particular Ship Types; Fishing Vehicles; Yachts; Answers to problems; Index.
Includes bibliographical references (p. 705-708) and index.
Keywords: Naval architecture; Electronic books